Naked Eye Chemosensing of Anions by Schiff Bases. (11th April 2022) - Junaid, Hafiz Muhammad; Batool, Madeeha; Harun, Farah Wahida; Akhter, Muhammad Saleem; Shabbir, Nabila
Abstract: Spectacular color change during a chemical reaction is always fascinating. A variety of chemosensors including Schiff bases have been reported for selective as well as sensitive recognition of ions. This review explains the use of Schiff bases as color changing agents in the detection of anions. This magic of colors is attributed to change in the electronic structure of the system during reaction. Schiff base chemosensors are easy to synthesize, inexpensive and can be used for visual sensing of different ions. Development of Schiff base chemosensors is commonly based on the interactions between polar groups of Schiff bases and ionic species and the process of charge transfer, electron transfer and hydrogen bonding between Schiff bases and ionic species cause the color of the resultant to be changed. Therefore, designing of simple Schiff base chemosensors which are capable of selective sensing of different anions has attracted considerable interest. In particular, naked eye sensing through color change is important and useful since it allows sensing of ions through color changes without using any instrumental technique. Highlights: Naked eye sensors are of much interest these days due to their visual detection properties rather employing complex instrumentation. Optical sensors are sensitive, selective, cost effective and robust. The magic of color change is fascinating factor in detection by these sensors. The color change may be attributed by interaction between anion and Schiff base by different mechanism i.e. electron transfer, charge transfer, hydrogen bonding, ICT etc. LOD data is an evidence of their great efficiency. Graphical Abstract: UF0001